Agaricus section Minores: New and noteworthy species from India - Arya, C.p.; Pradeep, C.k. (Phytotaxa, 2024)
In this study, four species of Agaricus sect. Minores are presented based on morphological and nrITS based phylogenetic analyses (Maximum Likelihood and Bayesian Inference). The molecular analysis and morphological characteristics supported the placement of these species in A. sect. Minores. Three species, viz., Agaricus indicus, A. palodensis, and A. wayanadensis are new to science, while A. purpureofibrillosus is a new phytogeographical record. Comprehensive descriptions, photographs, phylogenetic analyses results, and comparisons with related species are provided.